Pathar dye (paraphenyldiamine) poisoning: our experience of this lethal emerging health problem in a tertiary care centre - Nautiyal, Shivani; Tiwari, Shashwat; Ashutosh, Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: The aim of this case series study is to share our experiences regarding paraphenylenediamine (PPD) poisoning, its otolaryngological clinical presentation ,outcomes and need of tracheostomy in patients of hair dye poisoning at GSVM Medical College, Kanpur, U.P. Methods: This prospective study was carried out on 165 patients who presented in GSVM medical college Kanpur in period of December 2012 till December 2014. Data including demographic features (age, sex, marital status, socio-economic status), clinical features, laboratory findings, mode of intoxication (accidental or suicide) were collected and recorded. Results: A majority of the patients were young females (21-30 years) and belonged to a low socioeconomic class. The main cause was intentional suicidal ingestion. Cervicofacial edema, stridor, hoarseness of voice and pain in throat were initial symptoms. Tracheostomy was needed in 115 (69.69%) patients. Mortality of 21 (12.72%) patients was observeds. Conclusions: It is a major emerging health problem with high mortality. It is a medical emergency and early intervention is needed to save patient’s life. It is imperative to raise public awareness of the potential toxicity of the dye as well as to educate physicians about the need for aggressive and early treatment.